Perancangan Aplikasi Mobile Segar Sehat Untuk Penjualan Produk Hortikultura Kebun Rumah Tangga Komplek Karyawan Pt X Dengan Menggunakan Metode Human Centered Design - Chindy Elsanna Revadi; Kamson Sirait (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Food security is an important aspect during the COVID-19 pandemic, especially in the horticulture sector. However, with the existence of Large-Scale Social Restrictions as a government policy to avoid the spread of COVID-19, the customer is expected to be able to maintain a distance from physical trading activities, so horticultural marketing should be able to focus on the household segment by utilizing digital marketing. Based on this, the application design